(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Aims: Quality of life (QOL) is a subjective concept because the interpretation of each individual depends on his/her personal point of view. It is also multidimensional, given the influence of factors related to education, economy and socio-cultural aspects. Although the quality of life (QOL) of nursing students is a relatively well-researched topic in the West, there is a lack of it in developing countries like India. The aim of this study was to examine the QOL of Indian undergraduate nursing students and its associations with socio demographic and other parameters. Methods: This cross-sectional study was conducted in nursing college in Gujarat, India. In this institution undergraduate nursing students were selected. Usually, students start nursing program at 18 years of age. During the course of their study they learn different medical and paramedical related nursing subjects. Also, from the first year, they have their first direct clinical contact with patients in hospitals (scheduled clinical rotations). All the eligible subjects were approached after class hours to participate in the survey. Participation was completely voluntary. Informed consent was obtained from all individual participants included in the study. The questionnaires were anonymous, personally identifiable information such as name and identification number was not collected. Students were requested to sit at a fair distance from each other so as to assuage their privacy concerns. Students were assured of confidentiality and informed that the data collected shall be published and later would be provided to nursing education policymakers. The study was approved by the Institutional Ethics Committee and was conducted according to the ethical principles laid down by the declaration of ICMR. A cross-sectional study was conducted on 225 nursing students in Nadiad Gujarat, India. Students self-reported their QOL using the World Health Organization Quality of Life-BREF (WHOQOL-BREF).Data were collected on the individuals’ characteristics, including the year of study, substance use, physical exercise, academic performance, and other parameters. Results & Conclusion: The present study evaluates the quality of life of B.Sc nursing students of Dinsha Patel College of Nursing. On the basis of the findings the researchers concluded that the 146 students are perceived that they are live with average Quality of Life.